2001
DOI: 10.1136/heart.86.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levosimendan on myocardial contractility, coronary and peripheral blood flow, and arrhythmias during coronary artery ligation and reperfusion in the in vivo pig model

Abstract: Objective-To determine whether levosimendan, a calcium sensitiser that facilitates the activation of the contractile apparatus by calcium, improves myocardial contractile function during severe ischaemia and reperfusion without exacerbating the incidence of arrhythmias. Design-Pigs were pretreated orally twice daily for 10 days with 0.08 mg/kg levosimendan or placebo. On day 11 the left main coronary artery was ligated for 30 minutes, followed by 30 minutes of reperfusion. A bolus dose of levosimendan, 11.2 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
0
12
1
1
Order By: Relevance
“…The chronotropic effect of LEVO-infusion (0.2 mg/ kg/min) was more pronounced in our study than generally reported in patients with decompensated heart failure and in 30 kg pigs undergoing coronary ligation [18,35,36]. It probably represented a relative reflex tachycardia caused by vasodilatation as MAP was significantly reduced.…”
Section: Myocardioprotective Effect Of Levosimendancontrasting
confidence: 67%
“…The chronotropic effect of LEVO-infusion (0.2 mg/ kg/min) was more pronounced in our study than generally reported in patients with decompensated heart failure and in 30 kg pigs undergoing coronary ligation [18,35,36]. It probably represented a relative reflex tachycardia caused by vasodilatation as MAP was significantly reduced.…”
Section: Myocardioprotective Effect Of Levosimendancontrasting
confidence: 67%
“…Others have reported that LEV is less arrhythmogenic than the traditional inotropes (Follath et al 2002, Nieminen 2003 or that LEV has an electrophysiologically neutral profile (Nijhawan et al 1999, Lilleberg et al 2004. Also in experimental animal studies the results are inconsistent (Du Toit et al 1999, du Toit et al 2001, Lepran & Papp 2003. In light of the novel data in this study and the lack of agreement in previous publications, this potential adverse effect of LEV in post-MI HF should be examined carefully in the future.…”
Section: Discussionmentioning
confidence: 53%
“…The effects were blocked with the KATP channel blocker glyburide (Kersten 2000). In pigs, during 30 min of coronary artery occlusion and 30 min of reperfusion, levosimendan initiated in advance of ischemia improved global cardiac performance and coronary flow in the peripheral ischemic zone as compared to control (du Toit 2001). No difference versus control was found on the myocardial tissue concentrations of ATP, and there were an increased number of arrhythmias in the levosimendan group (du Toit 2001).…”
Section: Levosimendanmentioning
confidence: 99%